FORMALISASI SYARIAH = DOMINASI NALAR NEGARA: Studi atas Dominasi Nalar “State” Terhadap Islam Pasca Reformasi di Indonesia - M. Sholihin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
The paper aim to analyze the logic state, that applied for Islam in the post-reform era in Indonesia. And the formalization of sharia in conjunction with the state of reason, could be focussing of analysis. By using the interpretive approach, supported by the theory of